The voluntary precariat in the value chain: The hidden patterns of home-based garment production in Turkey. (February 2018) - Tartanoğlu, Şafak
This article explores the organizational characteristics and distinctive settings of the labour process of home-based garment work in the context of embedded control and consent relations in local garment productions in Turkey. Using Turkey as the case example of a garment export country in the global economy, the article explores the nature and organization of home-based piecework at the micro level within a broader global garment production chains perspective. Conducted in two Turkish cities, the study analyses the different cultural backgrounds of female workers and two distinct types of work, namely hand stitching and machine sewing of garments. The findings highlight the relationship between the cultural backgrounds of workers and the different types of work they undertake with control and consent practices as well as the patriarchal societal structure and relations in the context of local labour control regimes.